Measuring quantumness: from theory to observability in interferometric setups - Ferro, L; Fazio, R; Illuminati, F; Marmo, G; Pascazio, S; Vedral, V (EDP Sciences, 2018)
We investigate the notion of quantumness based on the noncommutativity of the algebra of observables and introduce a measure of quantumness based on the mutual incompatibility of quantum states. We show that such a quantity can be experimentally measured with an interferometric setup and that, when an arbitrary bipartition of a given composite system is introduced, it detects the one-way quantum correlations restricted to one of the two subsystems. We finally show that, by combining only two projective measurements and carrying out the interference procedure, our measure becomes an efficient universal witness of quantum discord and nonclassical correlations.